Rural Youth Strategies for Entering Adulthood in Asian Countries - Długosz, Piotr (INSTED: Interdisciplinary Studies in Education & Society, 2018)
The question of entering adulthood is discussed mainly in the context of urban youth from middle classes in Europe and North America. There is a lack of information about adulthood in countries where rural societies prevail. This article aims at presenting knowledge about entering adulthood in traditional societies in Asia. A secondary research of survey data from the research conducted among youth between 14 and 29 years of age in Uzbekistan, Kazakhstan, Kyrgyzstan and Georgia was undertaken in order to find an answer to the question regarding strategies for entering adulthood and factors having impact on this process. The "Big Five" model in which entering adulthood means finishing education, taking up a job, starting a family, having children and running an independent household was applied in the analysis of this phenomenon. The results of analyses indicate that the youth in subjective terms prefer traditional forms of adulthood based on a family. By analysing classic criteria of adulthood, it was determined that the majority of young people have failed to attain the status of adulthood yet. The conducted analyses have also shown differences in entering adulthood between rural and urban youth.